Enculturation in The Life Pattern of Breast Cancer Patients: An Ethno-Nursing Study on Sundanese Women - Witdiawati, Witdiawati; Rahayuwati, Laili; Sari, Sheizi Prita (Jurnal Ners, 2017)
Introduction: Death of breast cancer remains the highest position in the totem of incidents not only in Indonesia but also in the world. Its treatment process, which in fact brings huge impacts to the life quality of breast cancer patients in terms of physique, psychology, and social life, shapes a number of behavioral patterns throughout their life. The aim of this research is thus to explore patterns of breast cancer patients in sustaining their lifespan. Methods: This research is designed using ethno-nursing qualitative approach. The sampling technique is done purposively to 6 informants, all of whom are breast cancer patients in Garut District, West Java, Indonesia. Data collecting is done through interviews and participatory observation. Data transcription is analyzed using ethno-nursing analysis method. Results: The result of the research shows four domains occurring as a pattern of inculturation of breast cancer patients in Sundanese culture, namely 1) dedication as wife and mother of Sundanese breast cancer patients, 2) medicine seeking for the rest of their life, 3) factors affecting to breast cancer patients adaptation for daily routines, and 4) family gathering as a meaning for end of life. Discussion: The result of this research shows an interconnected cultural pattern in the life of these patients. It is thus advised that nurses provide service to breast cancer clients by applying nursing care inherent to their cultural values.